2020
DOI: 10.1371/journal.pone.0235404
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum inflammatory cytokines and berberine in the insulin signaling pathway among women with polycystic ovary syndrome

Abstract: Objective To study the role of selected serum inflammatory cytokines and berberine in the insulin signaling pathway among women with polycystic ovary syndrome (PCOS). Methods Selected serum inflammatory cytokines were analyzed in the particle cells, which were interfered by berberine, from 78 infertile women who were to be treated with In Vitro Fertilization (IVF) /Intracytoplasmic Sperm Injection-Embryo Transfer (icsi-et). Among them, 49 patients had PCOS infertility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…mTOR expression in granulosa cells of PCOS patients has also been investigated. A recent study showed that granulosa cells of PCOS patients had higher mTOR expression and phosphorylation than those of non PCOS patients; this mTOR expression could be reduced by berberine, a quaternary compound extracted from plants regulating glucose metabolism [ 20 ]. Another study found that mTOR expression in luteal granulosa cells was similar in PCOS patients and healthy individuals, but it was less in luteal granulosa cells in PCOS patients than in controls upon stimulation with insulin [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…mTOR expression in granulosa cells of PCOS patients has also been investigated. A recent study showed that granulosa cells of PCOS patients had higher mTOR expression and phosphorylation than those of non PCOS patients; this mTOR expression could be reduced by berberine, a quaternary compound extracted from plants regulating glucose metabolism [ 20 ]. Another study found that mTOR expression in luteal granulosa cells was similar in PCOS patients and healthy individuals, but it was less in luteal granulosa cells in PCOS patients than in controls upon stimulation with insulin [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine has been found to be safe and effective in terms of improving insulin resistance (IR), increasing ovulation rate per cycle, increasing the live birth rate, lowering body weight, and improving blood lipids [ 24 ]. Berberine can treat PCOS by regulating insulin signaling pathway and increasing insulin sensitivity [ 25 ]. Berberine also has the potential to treat PCOS of rat model through upregulating GLUT4 via activating PI3K/AKT and suppressing MAPK pathway [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kuang et al in their study investigated the effect and mechanism of inflammatory cytokines in serum (including IL6) on PCOS sensitivity to insulin. Women with PCOS were affected by subclinical inflammation leading to insulin resistance contributing to abnormal ovulation and problems with fertilization [28]. Overexpression of this gene is also noticeable in malignant tumors of the ovaries, e.g.…”
Section: Discussionmentioning
confidence: 99%